S72 Improving lung cancer survival in England evidenced through multiple data sources. (12th November 2015) - Beckett, P; Woolhouse, I; Walters, S; Benitez-Majano, S; Muller, P; West, D; McPhail, S; Broggio, J; Peake, MD
Abstract : Introduction: We have collated data from several sources to demonstrate that efforts made over the last 10 years to use data to drive service improvement and improved patient outcomes for UK patients with lung cancer have been successful. Methods: We used data submitted to the National Lung Cancer Audit (NLCA), National Cancer Registration Service (NCRS), Office for National Statistics (ONS) and Society of Cardiothoracic Surgeons (SCTS) from 1995–2013. We calculated numbers and proportions undergoing surgery, case-mix adjusted hazard ratios for death, and actual and predicted (using hybrid analyses) 1-year and 5-year survival for lung cancer patients in England. An international comparison has been made using data from the CONCORD-2 study. Results: In the NLCA, the proportion of NSCLC patients undergoing resection has risen from 14% (2005) to 23% (2013). Over this period, annual primary lung cancer resections have risen from 3, 220 to 6, 713. NLCA data, adjusted for age, sex, stage and PS, indicates a gradually falling hazard ratio for death (2013 HR 0.87, 95% CI 0.85–0.89 compared to 2008). ONS data demonstrates a gradual improvement in both 1 yr and 5 yr, and mirrors the increase in the number of resections carried out over the lifetime of the NLCA. Comparison of 1YS with other countries suggests that England has passed the survival measured in Denmark in 2004–07 (35%), but still lags behind Canada (42%) and Sweden (46%). In another analysis using NCRS data, comparing stage-specific 1 yr survival in England in 2004–07 and 2012, improvements are most marked in patients with early stage disease. Conclusion: Whilst many changes have taken place in the management of lung cancer over the last 10 years, the close temporal association between the date of the first NLCA report (2005), the numbers of resections carried out and the significant improvements in 1 and 5 yr survival (weighted towards earlier stages) and mortality we report here, would strongly suggest that the NLCA has been successful in its aim to improve standards of care and outcomes for patients. These improvements in survival bring England close to parity with other westernised countries, though there is still more work to do.